2021
DOI: 10.7759/cureus.15516
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of MRI in Evaluating Response After Neoadjuvant Systemic Therapy in Operable Breast Cancer

Abstract: Background Neoadjuvant chemotherapy (NAC) is an important step in the treatment of various types of breast cancer by downsizing the tumor to make it operable. Determining disease extent after NAC is essential for accurate surgical planning. MRI has been the gold standard for detecting tumors that are usually difficult to detect on ultrasound or mammography. However, the use of MRI after NAC is controversial. Therefore, we aimed to evaluate the diagnostic accuracy of post-NAC MRI in the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…33 It was found that the accuracy of MRI in detecting the residual disease after NAC differs according to the pCR definition and is higher when considering the absence of the invasive disease only. 34 It was also found that underestimation of the residual disease is more common in non-mass-forming lesions than in mass-forming lesions. 35 Non-mass lesions can manifest as small areas of patchy enhancement, and the differentiation between these areas and areas of nonmalignant enhancement may be difficult.…”
Section: Discussionmentioning
confidence: 98%
“…33 It was found that the accuracy of MRI in detecting the residual disease after NAC differs according to the pCR definition and is higher when considering the absence of the invasive disease only. 34 It was also found that underestimation of the residual disease is more common in non-mass-forming lesions than in mass-forming lesions. 35 Non-mass lesions can manifest as small areas of patchy enhancement, and the differentiation between these areas and areas of nonmalignant enhancement may be difficult.…”
Section: Discussionmentioning
confidence: 98%
“…Radiology studies continue to demonstrate inconsistencies in the imaging features as predictors of pCR. A recent survey of MRI imaging proved that MRI post-NACT remains inaccurate in replacing pCR [23]. On the other hand, studies have shown that tumor grade and hormonal status play a role in pCR rates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, WL was done for the non-palpable microcalcifications identified on her post-NAC mammograms by the Attending Radiologist (ADO). While MRI is usually the imaging modality of choice to monitor response to neoadjuvant therapy [30], mammography or ultrasound guidance is usually preferred for WL [27]. Extensive lesions and calcifications, especially those that exceed the borders of a mass, frequently require mammographic guidance and multiple wires for bracketing [27,31,32].…”
Section: Localization Of Non-palpable Lesionsmentioning
confidence: 99%